A Review of Plastic Bricks as a Construction Material (OCEM Journal of Management, Technology & Social Sciences, 2023)
Plastic brick is the form of brick manufactured from the combination of non-recyclable waste plastic with other constituents (sand, aggregate, cement, water, stone dust, fly ash, etc.) This study aimed to examine the research findings on transforming waste plastic into bricks that might be used to replace traditional bricks. Different journal articles were reviewed entitled the transformation of waste plastic into bricks to replace traditional clay bricks. Different open-access journal articles were searched to fit the topic of this study. The results indicate that the concrete blocks made with plastic bottles have 57% higher compressive strength and which was cited seventy-nine times by the other researchers (n = 79) "Use of recycled plastic water bottles in concrete blocks". The results further show that the compressive strength and other properties can be increased significantly when plastic is used as a binder with sand. But when it is used as filler, it produces competitive strength as ordinary bricks and can be used without any restrictions or hesitation. The main reflection of this review is to conduct primary research on a large scale to find an innovative model to transform waste plastic into environmentally friendly bricks. The implication of this study would be beneficial to students, future researchers, the Engineering Department of Oxford College of Engineering and Management, Gaindakot 2 in Nawalparasi district and young academicians.